2015
DOI: 10.1088/0741-3335/57/7/075011
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of laser to x-ray conversion by a double-foil gold target

Abstract: A novel double-foil configuration is proposed to improve the laser to x-ray conversion efficiency from laser irradiating a solid target. One-dimensional radiation hydrodynamic simulations show that the total x-ray conversion efficiency for the double-foil target is as high as 54.7%, which has a 10% improvement compared with the normal target. The improvement is mainly due to the enhanced soft x-ray emissions. Influences of the target geometry parameters on the x-ray conversion efficiency are investigated. Deta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…High-Z foam targets are hence predicted to be very favorable for indirect ICF, with good conversion efficiency and improved symmetry control [28]. Several other targets, including high-Z mixture target [29,30], even high-Z mixture foam target [31], double-foil gold target [32], and so on [33], have also been put forward as high brightness x-ray sources.…”
Section: Nuclear Fusionmentioning
confidence: 99%
“…High-Z foam targets are hence predicted to be very favorable for indirect ICF, with good conversion efficiency and improved symmetry control [28]. Several other targets, including high-Z mixture target [29,30], even high-Z mixture foam target [31], double-foil gold target [32], and so on [33], have also been put forward as high brightness x-ray sources.…”
Section: Nuclear Fusionmentioning
confidence: 99%
“…In the context of indirect drive ICF scheme, use of short wavelength laser [10][11][12][13][14][15] , high-Z targets 16,17 , long pulse duration 18,19 , mixture/cocktail [20][21][22][23][24][25] are proposed to enhance the conversion efficiency in the range of multi-eV to multi-keV. Recently, various other methods like CH foam coated gold targets 26 , low density high-Z foam target 27,28 , double foil (DF) target 29 , counter propagating (CP) laser beams irradiation 30 , sandwiched target [31][32][33] , multi-layer target 34 and DF target irradiated with CP laser beams 35 are considered to increase the conversion efficiency. In the field of multi-keV emission, different types of target geometries, including pre-exploded metallic thin foils 36,37 , high-Z liner 38 , mid-Z or high-Z doped aerogels 39,40 , etc.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is found that the cavity target, lower intensity, short wavelength, and long-pulse laser help increase x-ray radiation, and cocktail or sandwich hohlraum walls also increase x-ray intensity [2,4,[13][14][15]. Furthermore, double-foil gold targets, low-density targets, and high-Z mixture targets have been adopted to increase laser-to-x-ray CE [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%